Massive bilateral Wilms tumor and an effective therapy - case report - Robert Ściślak; Agnieszka Wójtowicz; Karolina Widłak; Joanna Nurzyńska-Flak (Kazimierz Wielki University, 2019)
Introduction. Wilms' tumor is one of the most common cancer arises into an abdomen and it is estimated to be over 90% of all pediatric kidney tumors. The tumor usually arises in a single kidney. Aim of the work. The aim of our study was to present diagnostics and treatment of massive bilateral Wilms' tumor in a child with abdominal enlargement without any other symptoms. Material and methods. The case repot is about the 10-months-old boy hospitalized due to enlargement of the abdomen. All diagnostics and treatment was managed by University Children's Hospital in Lublin. Case report. A 10-years-old boy was admitted to the hospital due to rapid abdominal enlargement. CT scan revealed massive bilateral tumor derived from kidneys. Considering clinical picture and additional tests it was decided to recognize the bilateral Wilms' tumor and implemented chemotherapy according to SIOP 2001 and changed to Umbrella protocol because of inefficiency. A right partial and left nephrectomy was conducted. Post-surgical chemotherapy was applied and finished without complications. There is no recurrence of disease. Kidney functioning is good. Discussion. The case is asymptomatic abdominal enlargement what is common in patients with Wilms' tumor. Abdominal pain is the most common initial presenting symptom. Picture diagnostic as a CT and US, gives first tip for diagnosis. Clinical picture and CT scans allow to apply chemotherapy. Surgery is essential in the treatment. In bilateral disease kidney function is essential. NSS is recommended. Conclusions. The only symptom the of the huge tumor was enlargement of the abdomen. In a few cases Wilms's tumor is bilateral and not responding to standard chemotherapy. Partial nephrectomy can provide complete remission and good kidney function.